Respuesta :
12q +3r =15
3(4q +r) = 3*5
Divide both sides by 3
4q +r = 5
Time for the second one:
-4q -4r = -44
-4(q +r) = (-4)*11
Divide both sides by -4
q +r = 11
4q +r = 5
q +r = 11
Subtract the second from first equation
3q 0 = -6
3q = -6
q = -6/3 = -2
q = -2
q +r = 11
-2 +r =11
r = 11 +2
r = 13
q = -2
r = 13
Your answer is...
(-2,13)
3(4q +r) = 3*5
Divide both sides by 3
4q +r = 5
Time for the second one:
-4q -4r = -44
-4(q +r) = (-4)*11
Divide both sides by -4
q +r = 11
4q +r = 5
q +r = 11
Subtract the second from first equation
3q 0 = -6
3q = -6
q = -6/3 = -2
q = -2
q +r = 11
-2 +r =11
r = 11 +2
r = 13
q = -2
r = 13
Your answer is...
(-2,13)
Solution of equation is (-2, 13)
Given that:
Equation;
12q + 3r = 15 ...... Eq1
-4q - 4r = -44 ...... Eq2
Find:
Solution of equation
Computation:
12q + 3r = 15.... Eq1 / 3
4q + r = 5 ..... Eq3
-4q - 4r = -44 ...... Eq2 / 4
-q - r = -11.......... Eq4
Eq3 + Eq4
3q = -6
q = -2
-q - r = -11
2 - r = -11
r = 13
Solution of equation is (-2, 13)
Learn more:
https://brainly.com/question/21105092?referrer=searchResults